Recent Advances in Neurodegeneration - Borreca, Antonella (IntechOpen, 2019)
This Edited Volume Recent Advances in Neurodegeneration is a is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of neurodegeneration. The book comprises single chapters authored by various researchers and edited by an expert active in the neurodegeneration research area. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on neurodegeneration, and open new possible research paths for further novel developments.